A Discrete Choice Experimental Approach to Understand Sports Event Tourists' In-Stadium Beer Consumption Preferences. (September 2021) - Lyu, Seong Ok; Hwang, Jinsoo
While drinking beer is an important component of sports event tourists' ceremonial behaviors, there is surprisingly limited information regarding what features of beer service offerings at professional sporting events are most preferred. Using a sample of sports event tourists attending South Korean professional baseball games, the main purpose of this study is to provide an opportunity for improved knowledge regarding how spectators show their willingness to pay for in-stadium beer services. Applying a discrete choice experiment, we also intend to identify spectators' heterogeneous preference systems, which vary depending on their levels of everyday alcohol use. Results suggest that respondents place great importance on serving temperatures and waiting time in line for purchasing beer at concession stands. The two drinker groups segmented based on the Alcohol Use Disorders Identification Test scores show different tastes for beer services. Several management implications are discussed to improve in-stadium entertainment and prevent alcohol-fueled misbehaviors.